1971
DOI: 10.1172/jci106656
|View full text |Cite
|
Sign up to set email alerts
|

The Protein and Lipid Composition of Arterial Elastin and Its Relationship to Lipid Accumulation in the Atherosclerotic Plaque

Abstract: A B S T R A C T Elastin preparations from intimal layers and the media of normal and atherosclerotic human aortae were analyzed for protein and lipid content. In atherosclerotic aortae, elastin from plaques was compared with elastin from adjacent normal appearing areas of the same aorta.Arterial elastin purified by alkaline extraction appeared to be a protein-lipid complex containing free and ester cholesterol, phospholipids, and triglycerides. The lipid component of normal arterial elastin was small (1-2%). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
4

Year Published

1973
1973
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(54 citation statements)
references
References 40 publications
6
44
0
4
Order By: Relevance
“…The striking increase in lipid content, particularly of ester cholesterol, as well as the increase in polar amino acids and the reduction in cross-linking amino acids observed in the alkali-extracted elastin of grade I and grade II plaques, are in agreement with previous observations (11). The differences in the amino acid composition involve amino acids which represent relatively small components of the isolated elastin preparations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The striking increase in lipid content, particularly of ester cholesterol, as well as the increase in polar amino acids and the reduction in cross-linking amino acids observed in the alkali-extracted elastin of grade I and grade II plaques, are in agreement with previous observations (11). The differences in the amino acid composition involve amino acids which represent relatively small components of the isolated elastin preparations.…”
Section: Discussionsupporting
confidence: 91%
“…Recent biochemical analyses of arterial elastin preparations have shown that the lipids accumulating on elastic membranes of atherosclerotic lesions are associated with the elastin protein of these elastic membranes, even in early atherosclerosis (11). The arterial elastin preparations were defined as that protein material which remained undegraded after alkali hydrolysis of arterial tissue homogenates.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid and mineral depositions in the aorta and aortic elastin fr. were similar to those in human atherosclerosis as described by Kramsch et al 13) Recently, Bennani-Kabchi et al 14) reported that vitamin D 2 and a high Ch diet administration induced advanced atherosclerotic lesions in the arterial wall with elevated oxidized LDL and calcification. These authors estimated that deposition of Ch, Ca and P in the aorta was affected by increases in lipid peroxides produced by vitamin D 2 , a vitamin E deficiency, and the atherogenic diet.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, elastase treatment was found to release considerable quantities of cholesterol from normal aortic intima and atherosclerotic plaque. Kramsch and Hollander 19 and others 2122 found that large amounts of cholesterol derived from LDL bind to elastin after a relatively brief (24-hour) incubation. Noma and colleagues 21 extended this work by demonstrating immunologically the presence of apoprotein B on the surface of LDL-incubated elastin.…”
Section: Location Of Lipidmentioning
confidence: 97%